A NEW IDENTITY IN THE FOLKLORE OF THE TRANSMIGRATION SOCIETY IN THE DHARMASRAYA REGENCY (IDENTITAS BARU DALAM FOLKLOR MASYARAKAT TRANSMIGRASI DI KABUPATEN DHARMASRAYA) - Samsiarni Samsiarni; Emil Septia; Yulia Sri Hartati; Armet Armet (Jurnal Gramatika, 2022)
Dharmasraya Regency is known for its multicultural society. The presence of transmigration communities to the area has made Dharmasraya a region with a very rich cultural diversity. There are two large groups that live side by side while maintaining their respective cultures, namely the Minangkabau people as natives and the Javanese as immigrants. The diversity of cultures that exist in Dharmasraya also affects the folklore that develops in the area, one of which is people's belief. This study uses a qualitative approach. so the purpose of this study specifically wants to show the trust of the transmigration community in Dharmasraya which is a multicultural society in relation to the social identity of the community towards a new identity. The results showed that in the folklore of the transmigration community there was a shift from the area of origin. If in the area of origin, folklore is magical and mystical, when mixed with a new society, folklore also changes its function into a new identity for the transmigration community which is the result of mixing indigenous peoples and transmigration communities.